From local to national metabolism: a review and a scale-up framework - Ningyu Yan (Taylor & Francis Group, 2020)
Research background: Countries are likely the most important subjects involved in the environmental control and response to global environmental issues, while the majority of the related metabolic analyses are focused on the metabolism at the city scale. Objective: Analyzing why and how to scale up the metabolic study from city to country. Methods: Combining quantitative analysis with a literature review socio-metabolic research, since it is an effective method to study resource and environmental issues and has been applied at different scales. Results: 1) A single city or a smaller area is hardly self-sufficient, and its sustainability and resilience needs the support of the surrounding environment; 2) At the country scale, systems exhibit a higher level of self-organization and a corresponding higher level of complexity, addressing the need for applying the metabolic theory at the national scale; 3) The emergy analysis methods show its advantages in study metabolic processes for national metabolism; 4) Input-output analysis plays an important role in and region coordination. Conclusions: The interactions among and within the scales are nested, as well as the goals and methods. Therefore, socio-metabolic research on scales differ in their priority goals, and the methods adopted must be targeted.